Impact of internal standard addition on dried blood spot analysis in bioanalytical method development. (October 2011) - Meesters, Roland; Hooff, Gero; van Huizen, Nick; Gruters, Rob; Luider, Theo
Background: Addition of internal standards to dried blood spot (DBS) specimens can be complicated. Therefore, we studied the feasibility of different internal standard addition procedures. Nevirapine and its stable-isotope analogue were used as model compounds and concentrations in DBS specimen were determined by matrix-assisted laser desorption/ionization-triple quadrupole tandem mass spectrometry using selected reaction monitoring.Results: The addition procedure of the stable isotope-labeled internal standard had significant impact on observed nevirapine concentrations. Relative recovery rates depending on the internal standard addition procedure ranged between 11.4 and 107.9%. Experiments with different punch sizes (5 and 7 mm diameter) showed no significant influence on observed nevirapine concentrations.Conclusion: Application of internal standard prior to blood spotting provided good nevirapine recoveries and this procedure is well suited for applying DBS in infectious diseases, especially in HIV-infection treatment.